MECHANICS OF VISCOUS WEDGES: MODELING BY ANALYTICAL AND NUMERICAL APPROACHES - Medvedev S. (My University, 2002)
Although complex rheological models have been used to study the evolution of orogenic wedges, many features of simple models remain to be fully explained. Here, we analyze the plane strain evolution of model orogenic wedges under simple boundary and rheological conditions. The uniform linear viscosity wedge is driven by motion of a basal boundary at a constant velocity. Three main analysis techniques are used: analytical (algebraic analysis of scales involved), semianalytical (thin sheet approximation), and a complete numerical approach. Application of this variety of approaches provides a better understanding of the underlying physics and outlines the advantages and disadvantages of the different techniques. The evolution of wedges can be divided into three phases. Initially, wedge growth is mainly vertical and symmetrical and depends little on the viscosity. The second phase exhibits almost self-similar growth with the appearance of surface extension, within an otherwise compressional system, and development of asymmetry. The last phase involves widening of wedge and further development of asymmetry and surface extension, the average slope of wedge decreases during this phase. The Ramberg number, the ratio of characteristic gravitational to shear stress, defines the duration of each phase. Several parameters introduced here (mean surface slope, asymmetry of the wedge, surface extension, and near-surface strain history) allow observations from natural wedges to be linked to the bulk viscosity of the model wedges. Analysis shows that the thin sheet approximation does not correctly describe the initial stages of wedge evolution.